Serial QuantiFERON testing and tuberculosis disease risk among young children: an observational cohort study. Issue 4 (April 2017) - Andrews, Jason R; Nemes, Elisa; Tameris, Michele; Landry, Bernard S; Mahomed, Hassan; McClain, J Bruce; Fletcher, Helen A; Hanekom, Willem A; Wood, Robin; McShane, Helen; Scriba, Thomas J; Hatherill, Mark
Summary: Background: The value of quantitative interferon-γ release assay results for predicting progression from Mycobacterium tuberculosis infection to active disease is unknown. We aimed to investigate the relation between QuantiFERON-TB Gold In-Tube (QFT) conversion interferon-γ values and risk of subsequent active tuberculosis disease and of QFT reversion. Methods: We analysed data from a reported vaccine efficacy trial of the tuberculosis vaccine MVA85A in South Africa. QFT negative, HIV uninfected young children aged 18–24 weeks were enrolled. We stratified participants by quantitative QFT result (interferon-γ <0·35 IU/mL, 0·35–4·00 IU/mL, and >4·00 IU/mL) at the intermediate study visit (day 336) and determined risk of progression to active tuberculosis disease over the subsequent 6–24 months. No QFT differences were observed between placebo and MVA85A groups at day 336 or end of study; therefore, both groups were included in analyses. Study clinicians were not masked to QFT values, but strict case definitions were used that excluded QFT results. We used generalised additive models to evaluate the quantitative relation between day 336 QFT value and subsequent disease risk, and we compared disease rates between QFT strata using a two-sample Poisson test. Findings: Among 2512 young children with QFT tests done at day 336, 172 (7%) were positive; 87 (7%) of 1267 in placebo group and 85 (7%) of 1245 in the MVA85A group (p=1·00). Compared with QFT non-converters (tuberculosis disease incidence 0·7 per 100 person-years [95% CI 0·4–1·1]), children with QFT conversion at interferon-γ values between 0·35–4·00 IU/mL did not have significantly increased risk of disease (2·5 per 100 person-years [95% CI 0·4–9·4]; incidence rate ratio (IRR) 3·7 (95% CI 0·4–15·8; p=0·23). However, QFT conversion at interferon-γ values higher than 4·00 IU/mL was associated with substantially increased disease incidence (28·0 per 100 person-years [95% CI 14·9–45·7]) compared with non-converters (IRR 42·5 [95% CI 17·2–99·7]; p<0·0001), and compared with children with interferon-γ values between 0·35–4·00 IU/mL (IRR 11·4 [95% CI 2·4–107·2]; p=0·00047). Among 91 QFT converters who were given a repeat test, 53 (58%) reverted from positive to negative. QFT reversion risk was inversely associated with interferon-γ value at QFT conversion and was highest with interferon-γ values less than 4·00 IU/mL (47 [77%] of 61). Interpretation: In young children, tuberculosis disease risk was not significantly increased, and QFT reversion was common, following QFT conversion at interferon-γ values up to 10 times the recommended test threshold (0·35 IU/mL). By contrast, QFT conversion at very high interferon-γ values (>4·00 IU/mL) warrants intensified diagnostic and preventive intervention because of the extremely high risk of tuberculosis disease in these young children. Funding: Aeras, Wellcome Trust, and Oxford-Emergent Tuberculosis Consortium (OETC) were the funders of the MVA85A 020 Trial. National Institute of Allergy and Infectious Diseases supported this analysis.